Traceback and Testing of Food Epidemiologically Linked to a Norovirus Outbreak at a Wedding Reception - Efstathia Papafragkou; Amanda Kita-Yarbro; Zihui Yang; Preeti Chhabra; Timothy Davis; James Blackmore; Courtney Ziemer; Rachel Klos; Aron J. Hall; Jan Vinjé (Journal of Food Protection)
We investigated a suspected norovirus outbreak associated with a wedding reception in Wisconsin in May 2015. Fifty-six of 106 (53%) wedding attendees were interviewed, and 23 (41%) reported symptoms consistent with norovirus infection. A retrospective cohort study identified fruit salad as the likely vehicle of infection (risk ratio 3.2, 95% confidence interval 1.1––8.3). Norovirus was detected by real-time reverse transcription polymerase chain reaction (RT-qPCR) in stool specimens collected from four attendees and one food handler and in 12 leftover fruit salad samples from both an opened and a sealed container. Norovirus-positive clinical samples (n = 4) were genotyped as GII.4 Sydney and norovirus-positive fruit salad samples (n = 2) confirmed the presence of GII.4 norovirus by Sanger sequencing with 98% nucleotide (n = 236) similarity in 5′ end of ORF2 between fruit salad and clinical specimens. In conclusion, this comprehensive norovirus outbreak investigation combined epidemiologic, virologic, and environmental findings to traceback the contaminated food as the source of the outbreak.